Organic Matter and Plant Nutrients in a Teak (Tectona grandis) Plantation - Kaul, O. N.; Sharma, D. C.; Tandon, V. N.; Srivastava, P. B. L. (Indian Forester, 1979)
Estimates of dry matter production and nutrient content of a 38 years old teak (Tectona grandis) plantation as obtained by the Mean tree technique and the Stratified tree tecbnique have been presented in this Paper. The total standing biomass as obtained by tbe Mean tree technique is abont 27% less Than that obtained with Stratified tree technique. A similar trend was observed when comparing the nutrient content of this stand by these two methods.